IMPLEMENTASI TUGAS DAN FUNGSI ARSIPARIS SEBAGAI PENGELOLA ARSIP DI LEMBAGA ARSIP NASIONAL REPUBLIK INDONESIA - Wiwin Irpina (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2021)
This study uses a qualitative method with a naturalistic approach to determine the duties and functions of archivists at the National Archives Institute of the Republic of Indonesia. Data collection is done through literature study, both primary and secondary data so as to be able to clarify various things found in qualitative research. Furthermore, theedata.analysisstechniques used..is a contents analysisstechnique where the.data analysis process begins before and during the data search process through the online website of the National Archives of the Republic of Indonesia which is then poured in the form of descriptive narratives and inductively summarizes the core. The duties and functions of archivists in carrying out work are reviewed in the perspective of Article 151 offthe Governmentt Regulation of the Republic off Indonesia. Number.28 of. 2012.concerning the.Implementationnof.Law.Numbere43 of 2009 concerningsArchives. The results show that the duties and functions of archivists at the National Archives of the Republic of Indonesia have been implemented as stated in Article 151 of the GovernmenteRegulation of.the. Republice of.Indonesia Number 28 of 2012 concerning the Implementatione of LawwNumbere43oof 2009 concerning Archives. The researcher recommends that the head of the National Archives of the Republic of Indonesia continue to provide guidance and developmenteofr archival humaneresources, one of which is through training, work motivation, application of quality standards ofkarchivist workebasedeonithe duties, functions and responsibilities of archivists so that they can make archives as a unifying node of the nation in the framework of the Unitary State of the Republic of Indonesia which is managed by professional and reliable archivists.Keywords: Duties and Functions of Archives, NationalwArchivesgof.thezRepubliceof Indonesia.